PENGARUH CASH RATIO, TIME INTEREST EARNED DAN DEBT TO EQUITY RATIO TERHADAP PROFITABILITAS (ROE) PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DALAM BEI PERIODE 2013-2017 - Angellia, .; Erlina, .; Moksa, Jana Jesifa; Wirawan, Joshua Andre; Wijaya, Novilia; Sitorus, Jessy Safitri; Stephanus, Andhy (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Financial performance can be measured by Return on Equity (ROE), because ROE is one of two base factors to determine company’s level of profit growth. A company can be identified success if the cash turnover is increasing along the certain financial period. If liquidity is increasing then the profit will increase because the changed value of current assets is getting increased by company’s current liabilities enchancement. The sample of research is 32( thirthy two companies ) Data collection method is using documentation method Data analysis thechnique used is descriptive quantitative analysis. Analysis model in this research is double linear regretion and using SPSS program. Data tested by classic assumption test, coefficient determination test, F test, and T test. The conclusion of this research both partial and simultaneous Cash Ratio ,Time Interest Earned, Debt to Equity Ratio are not influential to Return on Equity. The result of R coeffition determination is 7,3%. So this 7,3% variation of variable ROE can be explained by variation variable Cash Ratio ,Time Interest Earned, Debt to Equity Ratio Keywords: ROE, Cash Ratio, Time Interest Earned, Debt to Equity Ratio